Analysis of the Financial Condition of Insurance Companies PZU and Warta - Trippner, Paweł (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The insurance system is a very important element of the financial system of a state. As institutions of public trust, insurance companies play an important role in the process of transforming savings into investments, which directly affects the country’s economic development. Maintaining the insurance sector in a good financial condition guarantees stability of the financial system and economic development of Poland. The purpose of the paper is to present the essence of operations of insurance companies as financial institutions, present their role in the economy, and describe various methods of appraising their financial condition, presented in professional literature. In order to achieve this purpose, the research hypothesis was formulated, according to which the analysis of the financial condition (profitability) of insurance companies PZU and Warta gives the same results, using traditional (financial ratios), as well as alternative methods (the concept of Economic Value Added), and that smaller company (Warta) achieves higher level of operational efficiency than the larger company. The analysis conducted using both traditional (profitability ratios), as well as method of EVA confirmed the hypothesis, according to which PZU company is in better financial condition than one of the biggest competitors in insurance sector.